IMPLEMENTASI ALGORITMA J-BIT ENCODING PADA KOMPRESI FILE TEKS - Tedi Mizwar; Guidio Leonarde Ginting; Mesran Mesran; Alwin Fau; Soeb Aripin; Dodi Siregar (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2017)
Data is important and has a very important role in the activities of computer use. In general, the size of data that is at this time has a very large size. So at the time of sending large data through the network would lead to waste in the use of network resources when the data is accessed by other users and make the storage media more efficient in storing the data. In this study used J-BIT compression algorithm to reduce the size of text files, thus reducing the file size on storage media.